PELATIHAN PEMBUATAN HANDYCRAFT BERBAHAN DASAR LIMBAH CANGKANG MOLUSKA (KEONG DAN KERANG) DI DESA RANOOHA RAYA KECAMATAN MORAMO KABUPATEN KONAWE SELATAN PROVINSI SULAWESI TENGGARA - Fekri, Latifa; Ishak, Ermayanti; Asriyana, Asriyana; Nurgayah, Wa; Haya, La Ode Muhammad; Adimu, Hasan Eldin (Universitas Mataram, 2024)
ABSTRACT Bivalves and gastropods are two classes in the mollusk phylum which have the largest number of species compared to other classes. Organisms in this class are protected by a thick coat called a shell made from CaCo3 (calcium carbonate). The flesh of these organisms is used as food, while the shells are thrown away and sometimes not used, until they accumulate and become waste. Processing of shell waste has been carried out to fulfill various people's lives, including in the pharmaceutical, food industry, agriculture and craft industries. Handicrafts utilize various shell shapes with beautiful colors to produce several valuable products. This activity was carried out to guide and improve the skills of female fishermen in making handicrafts made from shell shells. This community service activity was carried out in Ranooha Raya Village, Moramo District, South Konawe Regency, and involved a partner group, namely a group of fishermen women who were still productive. The results of the service activities are handicrafts in the form of women's accessories such as brooches, key chains and bracelets. Keywords: Handycraft, shellfish waste, Ranooha Raya Village.